Group Decisions in Value Management - Utomo, Christiono; Murti, Farida; Idrus, Arazi (Makara Journal of Technology, 2015)
This research deals with a technique to expedite group decision making during the selection of technical solutions for value management process. Selection of a solution from a set of alternatives is facilitated by evaluating using multicriteria decision making techniques. During the process, every possible solution is rated on criteria of function and cost. Function deals more with quality than with quantity, and cost can be calculated based on the theoretical time value of money. Decision-making techniques based on satisfying games are applied to determine the relative function and cost of solutions and hence their relative value. The functions were determined by function analysis system technique. Analytical hierarchy process was applied to decision making and life-cycle cost analysis were used to calculate cost. Cooperative decision making was shown to consist of identifying agreement options, analyzing, and forming coalitions. The objective was attained using the satisfying game model as a basis for two main preferences. The model will improve the value of decision regarding design. It further emphasizes the importance of performance evaluation in the design process and value analysis. The result of the implementation, when applied to the selection of a building wall system, demonstrates a process of selecting the most valuable technical solution as the best-fit option for all decision makers. This work is relevant to group decision making and negotiation, as it aims to provide a framework to support negotiation in design activity.